Kecukupan zat gizi makro, status gizi, stres, dan siklus menstruasi pada remaja - Laras Sitoayu; Dewi Ayu Pertiwi; Erry Yudhya Mulyani (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: Adolescence is the transition period from children to adults which is characterized by the occurrence of changes in the body that allowed it to reproductive health problems. One of reproductive health problems is menstrual cycle disorders. Menstrual cycle disorder due to several factors including food intake, nutritional status, and stress.Objective: This research supposed to know the association the sufficient of macro-nutrients, nutritional status and stress with the menstrual cycle on adolescent at SMA Negeri Jakarta 21, 2016.Method: This design research is observation analytic with cross sectional approach. Sampling technique used proportionate random sampling and obtained 83 respondents adolescent. The technique of data collection used menstrual cycle questionnaire, DASS 14, food recall 3x24 hours (2 weekdays and 1 weekend), standardized food ingredient photos, and nutrisurvey.Results: There is 68.7% of respondents have an abnormal menstrual cycle. Based on statistical analysis of Chi-Square test, there is a significant relation between sufficient intake of carbohydrates (p=0.030), sufficient intake of protein (p=0.001), sufficient intake of fat (p=0.003), nutritional status (p=0,004), stress (p=0.000) and menstrual cycle. Based on logistic regression test results obtained the factors that most influence the menstrual cycle i.e. nutritional status (OR=20.16).Conclusion: Sufficient intake of macronutrients, nutritional status, and stress can affect menstrual cycle on adolescent, and nutritional status is the dominant factor that can affect the menstrual cycle.